Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Shreya

giải phương trình qui về phương trình tích

a/x\(^2\)+3x=0

b/x-2x\(^2\)=0

c/(x-7)(2x+3)=x(x-7)

d/(x-2)(x+3)=(x-2)(3x-1)

Nguyễn Lê Phước Thịnh
20 tháng 3 2023 lúc 21:41

a: =>x(x+3)=0

=>x=0 hoặc x=-3

b: =>x(1-2x)=0

=>x=0 hoặc x=1/2

c: =>(x-7)(2x+3-x)=0

=>(x-7)(x+3)=0

=>x=7 hoặc x=-3

d: =>(x-2)(3x-1-x-3)=0

=>(x-2)(2x-4)=0

=>x=2

Ngô Hải Nam
20 tháng 3 2023 lúc 21:41

a)

`x^2 +3x=0`

`<=>x(x+3)=0`

\(< =>\left[{}\begin{matrix}x=0\\x+3=0\end{matrix}\right.\\ < =>\left[{}\begin{matrix}x=0\\x=-3\end{matrix}\right.\)

b)

`x-2x^2 =0`

`<=>x(1-2x)=0`

\(< =>\left[{}\begin{matrix}x=0\\1-2x=0\end{matrix}\right.\\ < =>\left[{}\begin{matrix}x=0\\x=\dfrac{1}{2}\end{matrix}\right.\)

c)

`(x-7)(2x+3)=x(x-7)`

`<=>(x-7)(2x+3)-x(x-7)=0`

`<=>(x-7)(2x+3-x)=0`

`<=>(x-7)(x+3)=0`

\(< =>\left[{}\begin{matrix}x-7=0\\x+3=0\end{matrix}\right.\\ < =>\left[{}\begin{matrix}x=7\\x=-3\end{matrix}\right.\)

d)

`(x-2)(x+3)=(x-2)(3x-1)`

`<=>(x-2)(x+3)-(x-2)(3x-1)=0`

`<=>(x-2)(x+3-3x+1)=0`

`<=>(x-2)(-2x+4)=0`

\(< =>\left[{}\begin{matrix}x-2=0\\-2x+4=0\end{matrix}\right.\\ < =>x=2\)

乇尺尺のレ
20 tháng 3 2023 lúc 21:48

a)\(x^2+3x=0\)

<=>x(x+3)=0

x=0 hoặc x+3=0

x=0 hoặc x=-3

b)x-2x2=0

x(1-2x)=0

x=0 hoặc 1-2x=0

x=0 hoặc x=0,5

c)(x-7)(2x+3)=4(x-7)

(x-7)(2x+3)-4(x-7)=0

(x-7)(2x+3-4)=0

x-7=0 hoặc 2x+3-4=0

x=7 hoặc x=0,5

d)(x-2)(x+3)=(x-2)(3x-1)

(x-2)(x+3)-(x-2)(3x-1)=0

(x-2)(x+3-3x+1)=0

x-2=0 hoặc x+3-3x+1=0

x=2 hoặc x-3x=-3-1

               -2x=-4

               x=2